Innovations of knowledge management - Montano, Bonnie (IRRM Press, 2005)
Innovations of Knowledge Management highlights the broad range of topics that fall under the term knowledge management, thus emphasizing the large role knowledge management plays in organizations. As a compilation of some of the most recent work in the field, the included chapters truly present innovations in how organizations can and should manage their knowledge.